Efeitos cardiovasculares do ácido alfa-lipóico e do metilsulfonilmetano em ratos Wistar normotensos - Vitaliano, Allan Bezerra (2022)
Reactive oxygen species (ROS) are generated by cellular metabolism and are part of physiological, acting as signaling molecules or neuromodulators in the central nervous system, and pathological mechanisms. Angiotensin II (ANG II) stimulates ROS production which seem to mediate its dipsogenic and pressor actions. Alpha-lipoic acid (ALA), a potent antioxidant, reduces ROS production in several animal models of hypertension. Treatment with ALA lowers blood pressure and increases baroreflex sensitivity of 2 kidneys-1 clip renovascular hypertensive rats. Methylsulfonylmethane (MSM) has antioxidant activity, and a previous study has shown that this compound has beneficial hemodynamic effects in the pulmonary hypertension model. Thus, in the present study, we investigated the cardiovascular effects of ALA and MSM in normotensive Wistar rats. Wistar rats (290 - 310 g) were used to investigate: a) the change in systolic blood pressure (SBP) after oral administration (gavage) of vehicle, AAL (60 mg/kg), MSM (200 mg/kg) or AAL (60 mg/kg) combined with MSM (200 mg/kg) daily for 14 days; b) the effect of acute intraperitoneal administration of AAL (60 mg/kg) on the pressor response induced by ANG II (50 ng/0.1 ml). Treatment with only ALA significantly reduced the SBP of normotensive rats, but no significant changes were observed in the groups treated with MSM, alone or combined with ALA. Previous administration of ALA (60 mg/kg) did not alter the pressor response and reflex bradycardia induced by ANG II (50 ng/0.1 ml). ALA injection alone also did not change baseline mean arterial pressure and heart rate. Therefore, the present study shows that MSM has no effect on blood pressure. ALA, on the other hand, has a mild hypotensive effect when long-term administered. The results also suggest that ALA hypotensive response does not seem to be related to acute interference in peripheral angiotensinergic mechanisms.